Firearm injury hospitalizations and handgun purchaser licensing laws: longitudinal evaluation of state-level purchaser licensure requirements on firearm violence, 2000-2016 - Mitchell L. Doucette; Nicholas S. Meyerson; Cassandra K. Crifasi; Elizabeth Wagner; Daniel W. Webster (BMC, 2024)
Abstract Background Handgun purchaser licensing (HPL) laws mandate individuals to obtain a license from law enforcement before buying a firearm. Research indicates these laws effectively reduce various forms of fatal firearm violence, including homicides, suicides, and mass shootings. Our study sought to assess the impact of HPL laws on non-fatal firearm violence. Methods Utilizing the augmented synthetic control method (ASCM), we estimated the average treatment effect on the treated (ATT) resulting from a full repeal of an HPL law in Missouri (2007), a partial repeal in Michigan (2012), and an adoption on HPL law in Maryland (2013) on firearm injury hospitalizations. We utilized RAND's healthcare cost and utilization project-based dataset from 2000 to 2016 for our outcome variable. We conducted in-time placebo testing and leave-one-out donor pool testing as sensitivity analyses. Results Maryland's adoption was associated with a statistically significant 32.3% reduction in firearm-related injury hospitalization (FIH) rates (ATT = − 0.497, standard error (SE) = 0.123); Missouri's repeal was associated with a statistically significant 35.7% increase in FIH rates (ASCM = 0.456, SE = 0.155); and Michigan's partial repeal showed no statistically significant associations with FIH rates (ATT = − 0.074, SE = 0.129). Sensitivity analyses confirm the robustness of the estimated HPL effects. Discussion HPL laws appear to be protective against hospitalizations for nonfatal firearm injuries. These findings align with prior research indicating that HPL laws are effective in reducing fatal firearm violence. States without such licensing systems ought to consider these robust policies as a means to address firearm violence.